Changes in Plant Nutrient Concentration of Olive (Olea europaea L.) Leaves after Different Rates of Humic Acid Application - Sertaç Uyanık; Ali Sümer (Journal of Advanced Research in Natural and Applied Sciences)
This research was a one-year study to investigate how increasing rates of humic acid affect the nutrient elements [Nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), manganese (Mn), zinc (Zn) and copper (Cu)] of olive trees (Olea europaea) of 14 years old found in a private cultivation land located in Bozköy of Geyikli, Çanakkale (Latitude 35 S 431667, Longitude 4409876) in 2018. The humic acid used was a suspension of 15% humic and fulvic acid, which was a commercial product (Blackjak SC, pH 4-6). Different concentrations of humic acid [0 (control), 50, 100, 200, 400 mL tree-1] were applied directly to soil of 20-30 cm depth under canopy projection of trees after dissolving in 10 L of water in April. A randomized block design with four replicates and five doses was adopted on 20 trees. 200 leaf samples were taken in December from annual shoot tips as reciprocal leaf couples and nutrient element analyses were carried out. The macronutrient elements N and P significantly increased upon all humic acid applications. However, the changes in the elements K, Ca, Mg, Fe, Zn, and Mn were insignificant in all applications. Humic acid at all concentrations decreased copper in leaves. As a result, addition to routine farmer fertilization, humic acid application at the rate of 50 ml tree-1 was determined to be the sufficient dose for olive trees. Moreover, this mentioned dose is considered to be the most economical dose besides being the most suitable one.